Structural health monitoring & damage detection. Volume 7 : proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics 2017 - Niezrecki, Christopher (Conference proceedings of the Society for Experimental Mechanics series,, 2017)
Structural Health Monitoring & Damage Detection, Volume 7: Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the seventh volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Health Monitoring & Damage Detection, including papers on: Structural Health Monitoring Damage Detection System Identification Active Controls.